Marconi's Wireless and the Rhetoric of a New Technology - Toscano, Aaron. author. aut Link
XX, 145 p. 2 illus.
Keywords: This book examines the discourse surrounding the wireless, created by the Anglo-Italian inventor Guglielmo Marconi. The wireless excited early twentieth-century audiences before it even became a viable black box technology. The wireless adhered to modernist values—speed, efficiency, militarization, and progress. Language surrounding the wireless is a form of technical communication, overlooked by today’s practitioners. This book establishes a broader definition for technical communication by examining a selection of the discourse surrounding Marconi's wireless. The book’s main themes are the following: 1) technical communication is all discourse surrounding technology, 2) the field of technical communication (or technical writing) should incorporate analyses of discourse surrounding technologies into its epistemology, 3) the wireless is a product of the society from which it comes (early twentieth-century Western civilization), and 4) the discourse surrounding the wireless is infused with tropes of progress—speed, efficiency, evolution, and ahistoricity.